AB0076 Jak inhibitor baricitinib modulates human innate and adaptive immune system. (12th June 2018) - Kubo, S.; Nakayamada, S.; Ma, X.; Lee, S.; Yamagata, K.; Nakano, K.; Iwata, S.; Hanami, K.; Fukuyo, S.; Miyagawa, I.; Tamaki, Y.; Tanaka, Y.
Abstract : Background: Janus kinase (JAK), which constitutively binds to cytokine receptors, plays an important role in the cytokine signalling. While JAK is comprised of JAK1, JAK2, JAK3, and tyrosine kinase-2 (Tyk2), more than 40 types of cytokines transmit signals through JAK. After several clinical studies, baricitinib, a highly selective inhibitor of JAK1 and JAK2, has been approved recently for treatment of RA in Europe, Japan, and other countries. Although this drug is available orally due to its small molecular weight, it has comparable efficacy to the biological DMARDs (bDMARDs). Objectives: The present study was designed to determine the effects of a highly-selective JAK1 and JAK2 inhibitor, baricitinib, on human immunocompetent cells, in order to establish the significance of JAK and the potential for baricitinib in the therapeutic armamentarium against immune-mediated diseases. Methods: The effects of baricitinib and tofacitinib were evaluated using human monocyte-derived dendritic cells (MoDCs), plasmacytoid dendritic cells (pDCs), B cells and T cells. Results: The expression of costimulatory molecules CD80/86 on MoDCs were induced 48 hours after LPS stimulation. Baricitinib concentration-dependently suppressed the expression of CD80/CD86. Inhibition of CD80/CD86 expression by tofacitinib was comparable to that induced by baricitinib. pDCs stimulated for 5 hours with CpG produced both TNF-α and IFN-α. Baricitinib reduced the proportion of these IFN–α producing pDCs in a concentration-dependent manner. On the other hand, TNF-α production was not affected by baricitinib. Baricitinib also suppressed the differentiation of B cells into plasmablasts by B cell receptor (BCR) and type-I IFN stimuli, and inhibited the production of IL-6 from B cells. Tofacitinib also suppressed BCR- and IFN-α-induced plasmablast differentiation and IL-6 production. However, neither baricitinib nor tofacitinib altered IgG production by B cells. Human CD4 +T cells proliferated after T cell receptor stimulation with anti-CD3 and anti-CD28 antibody; however, such proliferation was suppressed by baricitinib in a concentration-dependent manner. In addition, baricitinib inhibited Th1 differentiation after IL-12 stimulation and Th17 differentiation by TGF-β1, IL-6, IL-1β and IL-23 stimulation. Tofacitinib showed similar effects in these experiments. In naive CD4 +T cells, IFN-α and IFN-γ induced phosphorylation of STAT1, which was inhibited by baricitinib as well as tofacitinib. Furthermore, IL-6-induced phosphorylation of STAT1 and STAT3 was also inhibited by JAK inhibitors. Conclusions: The present study demonstrated that JAK inhibitors affect innate and adaptive immunity in humans. They can fine-tune various immune networks through a variety of mechanisms and seem suitable potential therapeutic agents for the treatment of diverse autoimmune diseases. Disclosure of Interest: S. Kubo Speakers bureau: Bristol-Myers, Pfizer, and Takeda, S. Nakayamada Grant/research support from: Mitsubishi-Tanabe, Novartis and MSD, Speakers bureau: Bristol-Myers, UCB, Astellas, Abbvie, Eisai, Pfizer, Takeda, X. Ma: None declared, S. Lee: None declared, K. Yamagata: None declared, K. Nakano Grant/research support from: Mitsubishi-Tanabe and Eisai, Speakers bureau: UCB, Astellas, Mitsubishi-Tanabe, S. Iwata: None declared, K. Hanami: None declared, S. Fukuyo: None declared, I. Miyagawa: None declared, Y. Tamaki: None declared, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Chugai, Astellas, Eisai, Taisho-Toyama, Kyowa-Kirin, Abbvie, and Bristol-Myers, Speakers bureau: Abbvie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, Eli Lilly, GlaxoSmithKline, UCB, Teijin, MSD, and Santen